Asuhan Keperawatan Pada Tn. F Dengan Gangguan Sistem Integumen Luka Bakar Di Ruang RB-3 Rumah Sakit Umum Pusat H. Adam Malik Medan Tahun 2023 - Herianto Bangun (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2023)
Burns or Kombutio are damage to the skin or internal tissue caused by sunlight, hot liquids, fire, electricity or chemicals. The transfer of energy from the heat source to the body causes disfigurement or burns. Therefore, to reduce morbidity and mortality rates due to burns, health workers in this case, especially nurses, must provide comprehensive nursing care to sufferers, starting from promotion, prevention, treatment and rehabilitation. This writing aims to provide nursing care for combutio problems in the Ashoka Room of Haji Adam Malik Regional Hospital, Medan (North Sumatra). This Scientific Writing uses anamnesis and direct physical examination. It is hoped that the results of this scientific work will help society reduce the number of deaths and morbidity caused by burns inflicted on patients. The results of this research show that promotive efforts such as health education, sterile wound care, and pain management can reduce the number of morbidity and death in patients due to wounds. burn.